Variations of vileness: an introduction - Patterson, JHC; Wilton-Godberfforde, E (Routledge, 2017)
The guest editors explain how this special issue of Early Modern French Studies identifies and explores the significance of the vile in three key regards: i) the heuristic value of repulsive bodies; ii) a search for transcendent beauty in death and decay; iii) revilement along linguistic, social, and political lines. They argue that, within and between these wider phenomena, variations of vileness tellingly illuminate the difficulties of calibrating moral and aesthetic categories with those of a changing socio-political hierarchy.